Old Lithuanian interrogative particle biau - Ostrowski, Norbert (Baltistica, 2012)
Postpositioned particle jaũ, serving in Old Lithuanian as a focus marker, may have also followed question words. Paper presents the origin of the OLith. interrogative particle biau as a shortened form of be-jau (LKŽ 1, 735), cf. a similar process in Lith. niaũ-gi ‘really?’ < ne-jaũ-gi ‘really?’.